For the first limit, you can factor the numerator as a difference of squares:
[tex]x^4-1=(x^2-1)(x^2+1)[/tex]
and the first factor can be factored the same way:
[tex]x^4-1=(x-1)(x+1)(x^2+1)[/tex]
More generally, we have the formula
[tex]1+x+x^2+\cdots+x^n=\dfrac{x^{n+1}-1}{x-1}[/tex]
so really, for [tex]x\neq1[/tex],
[tex]\dfrac{x^4-1}{x-1}=x^3+x^2+x+1[/tex]
In any case, we get
[tex]\displaystyle\lim_{x\to1}\frac{x^4-1}{x-1}=\lim_{x\to1}(x+1)(x^2+1)=4[/tex]
For the second limit, you can factor the denominator by grouping:
[tex]x^3-x^2+x-1=(x^3-x^2)+(x-1)=x^2(x-1)+(x-1)=(x^2+1)(x-1)[/tex]
Then the limit is
[tex]\displaystyle\lim_{x\to1}\frac{x-1}{x^3-x^2+x-1}=\lim_{x\to1}\frac1{x^2+1}=\frac12[/tex]